Inverse problem for the heat equation in a rectangular domain - Ivanchov, N. I.; Kinash, N. Ye. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We establish conditions for the existence and uniqueness of a smooth solution to the inverse problem for the two-dimensional heat equation with unknown leading coefficient depending on time and the space variable.